Pilot Evaluation of a Residential Drug Addiction Treatment Combining Traditional Amazonian Medicine, Ayahuasca and Psychotherapy on Depression and Anxiety. Issue 5 (19th October 2020) - Giovannetti, Cecile; Garcia Arce, Sara; Rush, Brian; Mendive, Fernando
ABSTRACT: Recent research highlighted the therapeutic potential of ayahuasca, a psychoactive plant brew used ritually in traditional Amazonian medicine (TAM). The present study evaluates the impact of integrating ayahuasca and TAM with psychotherapy on depression and anxiety in an inpatient addiction treatment program. Male patients ( N = 31) were evaluated pre and post treatment using the Beck Anxiety Inventory (BAI) and the Beck Depression Inventory (BDI). Clinical and sociodemographic characteristics, motivation, quality of life, spirituality, and treatment satisfaction were also measured and analyzed by means of two tailed t -test, one way ANOVA and Spearman test. From pre- to post-treatment, patients showed significant reductions in scores of anxiety (from 20.8 to 11.6, p < .002) and depression (from 18.7 to 7.5, p <.001). Similarly, patients showed higher scores of quality of life ( p < .001) and spirituality ( p < .001) upon discharge, which correlated with their reduction in scores of anxiety and depression. While future results will evaluate the efficacy of this treatment on measures of addiction at follow-up, the present results build upon previous research to bring further support to the use of Ayahuasca and Amazonian medicine in mental health treatments with a transpersonal focus.